Paleodyction — a trase-fossil or physical phenomenon? - POPOVA, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The analysis of the publications concerning so-called Paleodictyon, together with the latest findings, has been suggested Paleodictyon genesis as a result of Rayleigh-Benard thermogravitative convection. This prosess is initiated by warming-up of the stratified masses of turbidites. In that's the case, biogenic hypothesis of Paleodictyon genesis, besides of it non-standing up to criticism from the biological point of view, is redundant.